SYNTHESIS AND CHARACTERIZATION OF CANINE PARVOVIRUS (CPV) VP2 W-7L-20 SYNTHETIC PEPTIDE FOR SYNTHETIC VACCINE - Derman, Serap; Kizilbey, Kadriye; Mansuroglu, Banu; Mustafaeva, Zeynep (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
Canine parvovirus (CPV) is a small, non-enveloped, single-stranded DNA virus of the autonomous Parvoviridae family that causes enteritis and myocarditis in canidae. Within the parvovirus group, CPV, mink enteritis virus (MEV) and feline panleukopenia virus (FPV) represent a set of host-range variants which infect dogs, mink family, cats or raccoons, and show over 98% amino acid homology. Tryptophan was also added to the N-terminus of peptide sequences for fluorescence spectrophotometry analysis. The aim of this article is the synthesis and characterization of W-7L-20 antigenic peptide sequence (W-QPDGGQPAVRNERA) of VP2 capsid protein of CPV with microwave-assisted solid phase peptide synthesis (SPPS) method. Crude synthetic peptide was purified by preparative RP-HPLC (Reversed Phase-High Performance Liquid Chromatography). Crude and purified peptides were analyzed comparatively by using a fluorescence spectrophotometer, and the purified peptide characterized by liquid chromatography-electro spray interface-mass spectrometry (LC-ESI-MS) with electro spray ionization. In this study, de novo peptide structure prediction server PEP-FOLD was used for construction of the 3D model of W-7L-20 peptide. The reason for selection of this peptide sequence is due to its immunogenic properties and its potential as synthetic peptide vaccine against canine parvovirus.
Keywords: Canine parvovirus (CPV); solid phase peptide synthesis (SPPS); microwave-assisted synthesis; synthetic peptide vaccine; PEP-FOLD; DE-NOVO PEPTIDE; Environmental Sciences & Ecology